FOREIGN STATE ECONOMIC POLICY IN THE CONTEXT OF ECONOMIC SECURITY - Нurochkina, Viktoriya; Makhanets, Liubov; Nahaieva, Olha; Rymar, Olha; Chornyi, Oleg; Shyshpanova, Nataliia (My University, 2021)
The world economy is characterized by the dynamic development and deepening of international relations. Under such conditions, the stable development of countries and guaranteeing economic security requires continuous adaptation to world trends by changing the priorities of foreign policy. The purpose of the study: to identify the features and directions of formation of foreign economic policy of the state in the context of ensuring its economic security, taking into account key factors of external influence. Research methods. The following methods are used in this article: axiomatic, statistical, correlation-regression, systematization and generalization. To achieve the goal of the article, the data of the EU statistical reports, the World Bank and individual countries for the study period of 10 years were selected, which allows to identify long-term trends in macroeconomic indicators. Results. The guidelines of the foreign economic policy of Poland, Denmark and Germany were studied and it was found that it is closely related to the protection of economic security from external influences. According to the results of correlation analysis, the influence of external economic factors on the volume of gross domestic product was established. According to the regression analysis, it was found that among a number of indicators of international relations that affect GDP, the most important is exports: the change in gross domestic product of Poland by 99% depends on changes in foreign supplies, Denmark - by 96% and Germany - 96 %. It is substantiated that in order to reduce the negative impact of these factors, the economic security of the country
Keywords: Foreign economic policy; Economic security; National security; Threats to economic security; Competitiveness.